Immuno-surveillance and protection of the human cochlea - Liu, Wei; Li, Hao; Kämpfe Nordström, Charlotta; Danckwardt-Lillieström, Niklas; Agrawal, Sumit; Ladak, Hanif M.; Rask-Andersen, Helge (Frontiers in Neurology, 2024)
Background: Despite its location near infection-prone areas, the human inner ear demonstrates remarkable resilience. This suggests that there are inherent instruments deterring the invasion and spread of pathogens into the inner ear. Here, we combined high-resolution light microscopy, super-resolution immunohistochemistry (SR-SIM) and synchrotron phase contrast imaging (SR-PCI) to identify the protection and barrier systems in the various parts of the human inner ear, focusing on the lateral wall, spiral ganglion, and endolymphatic sac. Material and Methods: Light microscopy was conducted on mid-modiolar, semi-thin sections, after direct glutaraldehyde/osmium tetroxide fixation. The tonotopic locations were estimated using SR-PCI and 3D reconstruction in cadaver specimens. The sections were analyzed for leucocyte and macrophage activity, and the results were correlated with immunohistochemistry using confocal microscopy and SR-SIM. Results: Light microscopy revealed unprecedented preservation of cell anatomy and several macrophage-like cells that were localized in the cochlea. Immunohistochemistry demonstrated IBA1 cells frequently co-expressing MHC II in the spiral ganglion, nerve fibers, lateral wall, spiral limbus, and tympanic covering layer at all cochlear turns as well as in the endolymphatic sac. RNAscope assays revealed extensive expression of fractalkine gene transcripts in type I spiral ganglion cells. CD4 and CD8 cells occasionally surrounded blood vessels in the modiolus and lateral wall. TMEM119 and P2Y12 were not expressed, indicating that the cells labeled with IBA1 were not microglia. The round window niche, compact basilar membrane, and secondary spiral lamina may form protective shields in the cochlear base. Discussion: The results suggest that the human cochlea is surveilled by dwelling and circulating immune cells. Resident and blood-borne macrophages may initiate protective immune responses via chemokine signaling in the lateral wall, spiral lamina, and spiral ganglion at different frequency locations. Synchrotron imaging revealed intriguing protective barriers in the base of the cochlea. The role of the endolymphatic sac in human inner ear innate and adaptive immunity is discussed.